The true quality of food proteins - Fursik, Oksana (My University, 2018)
The basis of the useful model is the task of conducting studies to determine the quality of protein in foods, there are many significant factors that affect the degree of assimilation and the possibility of further use of amino acids. Determining the quality of protein in foods is an important criterion for balancing the amino acid composition. Thanks to the stabilization of digestion and PDCAAS at a high level, adequate human nutrition is provided.В основу корисної моделі поставлена задача проведення досліджень визначення якості білка в харчових продуктах, наведено багато істотних факторів, які впливають на ступінь засвоєння і можливість подальшого використання амінокислот. Визначення якості білка в харчових продуктах є важливим критерієм для балансування амінокислотного складу. Завдяки стабілізації перетравності та PDCAAS на високому рівні забезпечується адекватне харчування людини.
Keywords: food proteins; essential amino acids; biological value; assimilation of protein; харчові білки; незамінні амінокислоти; біологічна цінність; засвоюваність білка; кафедра технології м’яса і м’ясних продуктів